2020
DOI: 10.2478/cait-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis of Tweets on Coronavirus Disease 2019 (COVID-19) Pandemic from Metro Manila, Philippines

Abstract: From the outbreak of a novel COronaVIrus Disease (COVID-19) in Wuhan to the first COVID-19 case in the Philippines, Filipinos have been enthusiastically engaging on Twitter to convey their sentiments. As such, this paper aims to identify the public opinion of Filipino twitter users concerning COVID-19 in three different timelines. Toward this goal, a total of 65,396 tweets related to COVID-19 were sent to data analysis using R Statistical Software. Results show that “mask”, “health”, “lockdown”, “outbreak”, “t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 50 publications
1
7
1
Order By: Relevance
“…Finally, negative emotions such as disgust, sadness, and anger exhibit the lowest score. This is in contrast to previous findings using a similar approach but conducted in the middle of the Covid-19 outbreak, which shows the dominating negative emotions were anger, fear, sadness, and surprise [18].…”
Section: Resultscontrasting
confidence: 99%
“…Finally, negative emotions such as disgust, sadness, and anger exhibit the lowest score. This is in contrast to previous findings using a similar approach but conducted in the middle of the Covid-19 outbreak, which shows the dominating negative emotions were anger, fear, sadness, and surprise [18].…”
Section: Resultscontrasting
confidence: 99%
“…This finding is similar to studies from other developing countries asserting that students experienced ineffective learning while in the middle of a pandemic (Comelli et al, 2021;Noori, 2021;Twinamasiko et al, 2021). At the start of the pandemic, many Filipinos expressed their negative sentiments and emotions such as anger, fear, sadness, and surprise (Garcia, 2020). Yet, regardless of their battles and challenges, both teachers and students have been actively pursuing the best mechanism to cope with the crisis.…”
Section: Pandemic and Coping Strategiessupporting
confidence: 86%
“…Similarly, Carracedo et al identified the current research lines developed around COVID-19 and the related business impact by adopting statistical analysis of extracted topics (Carracedo et al, 2021). Besides those academic content, other types of text content such as tweets or news articles (Osakwe and Cort es, 2021; are also analyzed by various text analysis techniques like sentiment analysis (Garcia, 2020), coding quantitative content analysis (De Caro, 2020), qualitative analysis (Nam and Nam, 2021). Although the text analysis techniques used in these studies differ, they all extract topic words or phrases to support the fundamental analysis.…”
Section: Literature Review 21 Analysis Of Various Contents Related To...mentioning
confidence: 99%